2003
DOI: 10.1021/nl0344155
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Wire Chemical Sensor Using a Microfabricated Tuning Fork

Abstract: We have measured the mechanical properties of a polymer wire bridged across the two prongs of a microfabricated tuning fork. The polymer wire is formed by stretching so that it has a built-in mechanical stress. Upon exposure to organic vapors, the stress in the polymer wire diminishes, which is sensitively detected from the changes in the resonance of the tuning fork. We have also shown that by trimming the polymer wire from micrometers down to nanometers the sensitivity and response improve considerably becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 24 publications
0
53
0
Order By: Relevance
“…Nanoindentation on the other hand can only provide information on the elastic modulus of nanofibers but it is easy to perform. [29] (c) Buckling of fiber using AFM WS 2 nanotubes [30] Nano-indentation (a) Elastic-plastic indention using AFM-based nanoindentation system Silver nanowires [31] (b) Elastic-plastic indention using AFM Silk [34] (c) Elastic indention using AFM Polyacrylonitrile (PAN) & PAN-CNT/graphite composite fibers [40,44] Polypyrrole [41] PLLA [45] Others (a) Electrically induced deflections in TEM CNTs [49] (b) Resonating wire bridged across prongs of microfabricated tuning fork Nitrocellulose/toluene sulfonamide formaldehyde resin [50] (c) Resonant contact AFM Polypyrrole [51,52] Silver & lead nanowires [52] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoindentation on the other hand can only provide information on the elastic modulus of nanofibers but it is easy to perform. [29] (c) Buckling of fiber using AFM WS 2 nanotubes [30] Nano-indentation (a) Elastic-plastic indention using AFM-based nanoindentation system Silver nanowires [31] (b) Elastic-plastic indention using AFM Silk [34] (c) Elastic indention using AFM Polyacrylonitrile (PAN) & PAN-CNT/graphite composite fibers [40,44] Polypyrrole [41] PLLA [45] Others (a) Electrically induced deflections in TEM CNTs [49] (b) Resonating wire bridged across prongs of microfabricated tuning fork Nitrocellulose/toluene sulfonamide formaldehyde resin [50] (c) Resonant contact AFM Polypyrrole [51,52] Silver & lead nanowires [52] …”
Section: Discussionmentioning
confidence: 99%
“…Boussaad et al [50] measured the mechanical properties of a polymer wire bridged across the two prongs of a microfabricated tuning fork. They made use of the resonant frequency of the tuning fork with the polymer wire to obtain the YoungÕs modulus of the nitrocellulose/toluene sulfonamide formaldehyde resin.…”
Section: Other Mechanical Characterization Techniquesmentioning
confidence: 99%
“…[259][260][261][262][263] Zhang et al have coated quartz tuning forks (with a resonance frequency of ∼ 33 KHz) with a thin PS layer from solution of varying concentration and showed a linear increase in the frequency shift with the mass attached on the tuning fork. [258] MTFs modified with anti-human IgG were applied to sense the binding of IgG within a range of 5-100 lg ml -1 .…”
Section: Tuning Fork Structuresmentioning
confidence: 99%
“…They demonstrated that the resonance frequency of the MTF/polymer nanowire structure is related to the Young's modulus of the polymer structure by E 2LK fork Af 0 Df 0 where L and A are the length and the cross sectional area of the polymer wire, K fork is the effective spring constant, f 0 is the resonance frequency, and Df 0 is the shift is the resonance frequency due to the presence of the polymer wire. [259] They have also shown reversible changes in the resonance frequency on exposure to organic vapors which can alter the elasticity of the polymer wire due to solvation effects. The technique has been further extended to achieve arrays of MTFs with different polymer wires to create a pattern of responses enabling the detection of various chemical vapors (water, ethylnitrobenzene, and ethanol vapors) with ppb level sensitivity.…”
Section: Tuning Fork Structuresmentioning
confidence: 99%
“…Therefore, and by consequence, the fabrication technique requires complex post-synthesis steps using sophisticated manipulating tools [12]. Furthermore, functionalization can only be performed as post-assembly processes [13]. The most common manipulation technique include atomic force microscopy (AFM) [14], random dispersion suspended onto pre-patterned electrodes [15], and lithographically patterning catalysts on electrodes [16].…”
Section: Introductionmentioning
confidence: 99%